Gaya Kepemimpinan Perempuan Dalam Instansi Publik: Studi Kasus Susi Pudjiastuti - Balkis, Aulia Hanadita (Jurnal Ilmu Administrasi Negara (JUAN), 2020)
Pros and cons of women’s leadership in Indonesia is a crucial issue that is always discussed every year. The strong stereotype of leaders that must come from male gender that is assertive and strong makes women leaders considered one eye in society. This study uses qualitative methods with analysis using secondary data. The results of this study are that gender has no effect on one’s leadership. Susi Pudjiastuti is a female leader in the Ministry of Maritime Affairs and Fisheries who is masculine in nature but is able to produce several programs that are beneficial for all fields. During his leadership, he managed to get work achievements that had never been obtained by the previous minister.